(3QSGdI aj hGLHGJ GdUdGI hSffgGs - (3eLghds
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg Gdhdj GdMejO GdeHOF GdeYjO TQY dYHGOg GdUdGI aEf GdJeGS ef ELGHJg ef CaVd GdWGYGJ hESYGag HbVGA MGLJg ef CbQH GdbQHGJ Cf CcJH QSGdI ehLRI JTJed Ydi hGLHGJ GdUdhGJ GdeaQhVGJ heG YSGg jSfM ef GdefOhHGJ s
(3BNQgG (B:s
(3aEPG GfbVJ JUGaMhG hJgGOhG (B( (3cPG (B) (3hKhGHgG eGFI Cda MLI hYeQI hjYWi eG ojSCd hHGbj GdUdhGJ GdefOhHGJ aj cJH GdCUMGH adjWdH ef gfGc hcd GdfhGad QcYJGf HJTgOs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3abg GdePGgH GdCNQis